2017
DOI: 10.1021/acscatal.7b00032
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Connected Carbon Nanotubes as Electrocatalysts for Hydrogen Evolution Reaction through Band Engineering

Abstract: Controlled assembly of mesoscopic structures can bring interesting phenomena because of their interfaces. Here, carbon nanotubes (CNTs) are cross-coupled via a C–C bonding through Suzuki reaction resulting in three-dimensional (3D) CNT sponges, and these 3D CNTs are studied for their efficacy toward the electrocatalytic hydrogen evolution reaction (HER) in acidic mediumone of the promising methods for the production of a renewable energy source, hydrogen. Both single and multiwall CNTs (SWCNTs and MWCNTs) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 38 publications
1
53
0
Order By: Relevance
“…In AChE-modified electrodes, a lower current response was observed ( Figure 4 b), assumed to be a result of slow electron transfer through BSA layers due to a low content of amino-acid-containing phenol backbones (e.g., tyrosine) [ 57 , 58 ]. Previous studies [ 32 , 59 , 60 , 61 ] have demonstrated that multiwall CNTs efficiently promote the electrocatalytic oxidation of thiocholine. As shown in chemical pathways (i) and (ii), thiocholine products undergo rapid dimerization to form the dithiobischoline dimer species.…”
Section: Resultsmentioning
confidence: 99%
“…In AChE-modified electrodes, a lower current response was observed ( Figure 4 b), assumed to be a result of slow electron transfer through BSA layers due to a low content of amino-acid-containing phenol backbones (e.g., tyrosine) [ 57 , 58 ]. Previous studies [ 32 , 59 , 60 , 61 ] have demonstrated that multiwall CNTs efficiently promote the electrocatalytic oxidation of thiocholine. As shown in chemical pathways (i) and (ii), thiocholine products undergo rapid dimerization to form the dithiobischoline dimer species.…”
Section: Resultsmentioning
confidence: 99%
“…Different synthetic ways have been developed to transform NCs into chemical platforms for further post‐functionalization reactions. Among these reactions, the Suzuki–Miyaura cross‐coupling has often been used and requires the presence of either a halogenated group (Cl, Br or I) or a boronic moiety on the carbonaceous surface . Following Tour's seminal report, the addition of different phenyl groups has been described (including iodophenyl or phenyl boronic acid) starting from the diazo derivative (Scheme ) .…”
Section: Methodsmentioning
confidence: 99%
“…The stacking results in av ery low dispersibility,a nu nfriendly manipulation and bad processability.D ifferent synthetic ways have been developed to transform NCs into chemical platformsf or furtherp ost-functionalization reactions.A mong these reactions, the Suzuki-Miyaura cross-coupling has often been used and requires the presence of either ah alogenated group (Cl, Br or I) or ab oronic moiety on the carbonaceous surface. [14][15][16][17] Following Tour's seminal report, the addition of different phenyl groups has been described (including iodophenyl or phenyl boronic acid) starting from the diazo derivative (Scheme 1). [15,18,19] An alternative to this method is the directg rafting of halogens.T he grafting of fluorine, [21] bromine [22][23][24] andi odine [25,26] through different reactions has been reported.…”
mentioning
confidence: 99%
“…To overcome this problem, it is necessary to explore new material or support material from Pt as an electrocatalyst. In the past years, several studies have been concentrating on novel nanostructure carbon material such as nanotubes 165,166 and nanofibers 167‐169 for catalyst supports in DMFC application due to their properties of low manufacture cost and good electronic conductivity. In particular, the specific morphology of 1D materials will enhance the stability of the support materials and increase the efficiency of the resulting anode and cathode electrodes.…”
Section: Fibrous Materials As Electrochemical Catalysts In Fuel Cell Applicationmentioning
confidence: 99%